The Construction of Identities in Xi Xi’s Works of Fiction - Goh, Kwee Eng (2009)
Xi Xi (1938--) is regarded as the most emblematic author in Hong Kong. She has been writing persistently since the 1950’s and has produced numerous pieces of works. This thesis is targeted to dissect the works of fiction produced by Xi Xi across different eras. It looks into the construction process of her widely-accepted local and female identities as well as the courses taken by her as a female Hong Kong author in constructing her unique and conspicious regional and gender identities, while sandwiched between two powerful forces of the Chinese and the British. This thesis carries out the discussion looking into three aspects. First, it probes into the cognizant elements of Hong Kong in Xi Xi’s works of fiction and analyzes her delicate observations and writings towards different aspects of the city. Next, it analyzes Xi Xi’s works that focus on females and discusses her creation of female identity. Lastly, this thesis combines Xi Xi’s identities as a Hong Kong citizen and a female to discuss about the common foundation and spiritual nature between the two, thus demonstrating that both the Hong Kong citizens and the females in Xi Xi’s works of fiction are in fact two facets of her single identity construction.